SPE Annual Technical Conference and Exhibition 2021
DOI: 10.2118/206288-ms
|View full text |Cite
|
Sign up to set email alerts
|

Novel Nano and Bio-Based Surfactant Formulation for Hybrid Enhanced Oil Recovery Technologies

Abstract: This investigation presents laboratory and field deployment results that demonstrate the potential candidacy utilizing Nano and bio-technologies to create superior chemicals for novel applications to increase oil recovery from both onshore and offshore reservoirs. Nano-technology is gaining momentum as a tool to improve performance in multiple industries, and has shown significant potential to enhance hydrocarbon production. The laboratory analysis and specifically designed coreflood results indicate there are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…This simultaneous application shows promise for enhancing oil recovery processes. [141,148] Ma et al [149] investigated the application of nanotechnology and biomaterials to enhance oil recovery. Their study demonstrated that nanoparticles, in synergy with biosurfactants and traditional surfactants, improved surface compositions, increasing oil transfer capabilities.…”
Section: Bio-nanomaterialsmentioning
confidence: 99%
See 2 more Smart Citations
“…This simultaneous application shows promise for enhancing oil recovery processes. [141,148] Ma et al [149] investigated the application of nanotechnology and biomaterials to enhance oil recovery. Their study demonstrated that nanoparticles, in synergy with biosurfactants and traditional surfactants, improved surface compositions, increasing oil transfer capabilities.…”
Section: Bio-nanomaterialsmentioning
confidence: 99%
“…The research also explored successful applications of nano-surfactant formulations and biomaterials in both field and lab settings, optimizing feasibility in terms of time and cost. [141,143,144,149] In general, the use of bio-nanomaterials in oil recovery, combining biotechnology and nanotechnology, enhances recovery processes with advanced chemicals. Natural biomaterials and unique nanoparticles improve oil movement, leading to more efficient and environmentally friendly extraction.…”
Section: Bio-nanomaterialsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, it has been discovered that biosurfactants and nanoparticles can be combined with synthetically produced surfactants to produce brand-new, more effective surface active agents for better oil recovery. Based on research in the literature, it was discovered that these formulations can improve the flow back of the injected stimulation fluids and further mobilise the oil to be extracted from the matrix and micro-fractures [108].…”
Section: In Preparation Of Micro-emulsion Systems and Nano-particlesmentioning
confidence: 99%